Transisi Demografi dan Pertumbuhan Ekonomi Indonesia: Perbandingan Antar Pulau di Indonesia - Nur Azura Rahmi; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study examines the relationship between demographic dynamics and economic growth across islands in Indonesia consisting of the island of Sumatera, Java, Bali-Nusa Tenggara, Kalimantan, Sulawesi, and Maluku-Papua from 2014 to 2023. Specifically, this study investigates the impact of productive-age population growth, dependency ratio, and capital growth on economic growth between island in Indonesia. Using panel data analysis with the Random Effect Model (REM) approach, the study findings reveal that the increase in the productive-age population and capital growth partialy has a not significant negative effect on between island in Indonesia economic growth. Meanwhile, the dependency ratio also has a negative effect on economic growth in Indonesia, although the impact is significant. Among these regions, Kalimantan shows the strongest economic performance, while the islands of Bali and Nusa Tenggara face the greatest challenges in utilizing their demographic dividends. These findings offer policy insights to optimize Indonesia's demographic transition.